2016
DOI: 10.14238/sp14.6.2013.341-4
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Kelainan Kongenital Anomali Gastrointestinal pada Neonatus dan Kematian

Abstract: Latar belakang. Kelainan kongenital anomali gastrointestinal merupakan kelainan defek morfologik saluran cerna yang dijumpai sejak bayi baru lahir. Tujuan. Mengetahui hubungan kelainan kongenital anomali gastrointestinal dan kematian neonatus.Metode. Studi potong lintang retrospektif dengan penelusuran rekam medis Departemen Ilmu Kesehatan Anak, RSUD Dr.Zainoel Abidin Banda Aceh sejak bulan Januari 2010-Desember 2011. Hubungan antar variabel dianalisis menggunakan uji X2dengan tingkat kemaknaan p<0,05.Hasil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…This is thought to be associated with the incidence of polyhydramnios. 1,16 F I G U R E 1 Abdominal radiograph images of total obstruction (A) and partial obstruction (B). 11 F I G U R E 2 True double bubble 11…”
Section: Gestational Agementioning
confidence: 99%
See 1 more Smart Citation
“…This is thought to be associated with the incidence of polyhydramnios. 1,16 F I G U R E 1 Abdominal radiograph images of total obstruction (A) and partial obstruction (B). 11 F I G U R E 2 True double bubble 11…”
Section: Gestational Agementioning
confidence: 99%
“…Kumar et al found that preterm pregnancy had a significant effect on child mortality. This is thought to be associated with the incidence of polyhydramnios 1,16 …”
Section: Prognosis Factors Of Mortalitymentioning
confidence: 99%